LEGITIMACY STRATEGIES OF THE POWER:SAN LUIS POTOSI WELCOMED THE PROGRESS MESANGGER IN 1888 (Tzintzun, Revista de Estudios Históricos, 2016)
In this article, it will be attempt to set up an analytical framework about thereactions to the development of the rail road system in San Luis Potosi in 1888,taking into count the legitimacy strategies used by the governing regime. Thestrategies were based on modernity and positivism. Firstly, we will tackle the keyconcepts in order to understand the events involved in the development of the railroad system in San Luis Potosi in 1888. Secondly, it will be attempt to put intopractice those key concepts in order to explain the specific situation like thepatriotic demonstration which took part during the grand opening of the Mexicanrail road system on November 2nd , 1888, according to our research , it projectedand legitimated the philosophy of the governing regime.
Keywords: order and progress; positivist ideals; modernity; celebrations